Conserver, restaurer : écrire le temps en Afrique - Pol Pierre Gossiaux (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
African Art, well represented in the collections and ethnographical museums, is most of the times an Art outside its cultural context. Hence, its restoration ends up frequently in esthetical and historical non-senses. Is it still possible to apprehend the meaning and function of these objects in order to restore and conserve them better?